APLIKASI BERBASIS FUZZY MULTIPLE ATTRIBUTE DECISION MAKING PENENTUAN JURUSAN PADA SMK SATU NUSA 1 BANDAR LAMPUNG - -, Sodikin -; -, Fitria (244-5567)
Fuzzy Multiple Attribute Decision Making is a method used to find the optimal alternative of a number of alternatives with certain criteria. The essence of FMADM is to determine the weight values for each attribute, followed by a ranking process will select the alternative that has been given. Basically, there are three approaches to find the value of attribute weights, namely subjective approach, objective approach and the integration approach between subjectively and objectively.Techniques of this study, the data will be in entrikan students ranging from no registration, name, address, phone, value mathematics, Indonesian, English, and interest, then this value criteria will be incorporated into the approach to Fuzzy Multiple Attribute Decision Making which is already available on application that is developed using J2SE, the application will output the majors recommendations. The results obtained from this study models and applications in determining the majors in one Nusa 1 SMK Bandar Lampung accurate, approach Fuzzy Multiple Attribute Decision Making can be used for the determination of the majors in one Nusa 1 SMK Bandar Lampung and Applications determination majors in one Nusa 1 SMK Bandar Lampung can be used as a reference and management students of SMK Bandar Lampung One Nusa 1 in determining the majors.Keyword: Fuzzy Multiple Attribute Decision Making, SMK Satu Nusa 1 Bandar Lampung.